A Low-Profile Antenna Based on Single-Layer Metasurface for Ku-Band Applications. (16th December 2020) - Abdulkarim, Yadgar I.; Awl, Halgurd N.; Muhammadsharif, Fahmi F.; Karaaslan, Muharrem; Mahmud, Rashad H.; Hasan, Sattar O.; Işık, Ömer; Luo, Heng; Huang, Shengxiang
Abstract : Improvement in the antenna gain is usually achieved at the expense of bandwidth and vice versa. This is where the realization of this enhancement can be made through compromising the antenna profile. In this work, we propose a new design of incorporating periodic metasurface array to enhance the bandwidth and gain while keeping the antenna to a low-profile scheme. The proposed antenna was simulated and fabricated in order to validate the results in the operating frequency range from 10 MHz to 43.5 GHz. Computer simulation technology (CST) microwave studio software was used to design and simulate the proposed antenna, while LPKF prototyping PCB machine was utilized to fabricate the antenna. Results showed that the antenna generated a gain and bandwidth of 14.2 dB and 2.13 GHz, respectively. Following the good agreement between the numerical and measurement results, it is believed that the proposed antenna can be potentially attractive for the application of satellite communications in Ku-band electromagnetic wave.